2017
DOI: 10.1136/bcr-2016-217964
|View full text |Cite
|
Sign up to set email alerts
|

Maternal bradycardia occurring prior to onset of HELLP syndrome in a woman with pre-eclampsia

Abstract: A 36-year-old nulliparous woman developed pre-eclampsia at gestational week (GW) 28 Cardiac status was checked regularly. Heart rate of 93 beats per minute (bpm) with left atrial diameter (LAD) of 35 mm, left ventricular hypertrophy and inferior vena cava diameter (IVCD) of 8 mm at GW 32 decreased to 48 bpm with an expanded IVCD to 25 mm, dilated left atrium (LAD to 39 mm), increased pulmonary arterial pressure, increased systemic vascular resistance (approximate 3000  dyn s/cm) and biphasic intrarenal venous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…While looking for speci c clinical characteristics to this clinical rare entity we observed that women with delayed postpartum preeclampsia had a relative sinus bradycardia as one of the clinical signs at presentation. Similar observations were reported in few case reports in both ante partum and delayed post-partum preeclampsia [6,7,8]. Therefore, the present study aimed to validate these observations and to compare maternal heart rate in delayed postpartum preeclampsia to normotensive women on the same postpartum day.…”
Section: Introductionsupporting
confidence: 82%
“…While looking for speci c clinical characteristics to this clinical rare entity we observed that women with delayed postpartum preeclampsia had a relative sinus bradycardia as one of the clinical signs at presentation. Similar observations were reported in few case reports in both ante partum and delayed post-partum preeclampsia [6,7,8]. Therefore, the present study aimed to validate these observations and to compare maternal heart rate in delayed postpartum preeclampsia to normotensive women on the same postpartum day.…”
Section: Introductionsupporting
confidence: 82%
“…This blood reservoir decreases with sympathetic activation, resulting in a rapid increase in venous return up to 800 mL. Preeclampsia is characterised by sympathetic overactivity,17 and ischaemia occurs in the splanchnic organs in severe forms of preeclampsia, such as the hemolysis, elevated liver enzymes and low platelet (HELLP) syndrome 22 23. Women with preeclampsia accounted for 67% (16/24) of women with HDP in this study (see footnote for table 1).…”
Section: Discussionmentioning
confidence: 66%
“…The mechanism of bradycardia in preeclampsia is unknown [ 4 , 5 ]. Our patient had normal electrolytes and no evidence of acute myocardial ischemia on electrocardiography and TTE.…”
Section: Discussionmentioning
confidence: 99%
“…Bradycardia, usually of modest-to-moderate severity given the clinical presentation, has been reported as a rare feature of preeclampsia; its mechanism, however, has generally been considered to be unknown [ 4 , 5 ]. The case reported here is illustrative of the potential for postpartum preeclampsia in an otherwise healthy young woman to present with a seemingly inappropriate relative bradycardia despite acute pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%